The Trouble With Fathers: The Impact of Time and Gendered-Thinking on Working Relationships Between Fathers and Social Workers in Child Protection Practice in England. (November 2019) - Philip, Georgia; Clifton, John; Brandon, Marian
The lives of families entering the child protection arena may be shaped by a range of troubles, including material deprivation, physical and mental health problems, and substance misuse or domestic abuse. Despite the interest in whole family approaches, the issue of how professionals fail to work effectively with fathers is long-standing and resistant to change. This article illustrates challenges in building working relationships with men, including the challenge of avoiding binary thinking in the assessment of fathers as "risk" or "resource." Drawing on our qualitative longitudinal study of men's experiences of child protection in England, we highlight how both organizational (clashing time perspectives) and cultural (gendered-thinking) factors can trouble the potential relationship between social workers and fathers. We argue for a more gender sensitive approach to social work practice, which can respond more fully and effectively to the experiences of fathers and mothers.